Synergy as a criterion for evaluation of projects revitalization of city centers - Derlatka, Adam (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
The purpose of this study was to discuss and analyze three projects of urban renewal within the city centre located in its cultural heritage. These projects were implemented as a part of revitalization programs and should result in a change of the entire degraded area. Consequently, the impact of these changes should bring synergy results to revitalize space and its surroundings. The paper focused on analysis and comparison of currently being developed revitalization programs in old town (Miasto Kazimierzowskie) of Radom and Rzeszów with already implemented project in Bielsko-Biała where synergy effect emerged thanks to very complex revitalization program. Another aim was to find out what is the potential synergy effect and how it can be achieved when preparing revitalization program for urban area placed in public area.